Design and Validation of a Questionnaire on Inclusive Practices with Technological Resources at University - Gallardo-López, José Alberto; Cotán Fernández, Almudena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The aim objective of this study is to design and validate a quantitative questionnaire. The instrument seeks to gather information from the perspective of university students with disabilities on the impact of technological resources on educational inclusion in Higher Education. The methodology is descriptive and correlational. From an initial design of the questionnaire, a content validation was carried out by expert judgment, improvements were applied and it was distributed to a sample of 110 university students with disabilities from six Andalusian public universities. After this, statistical validation tests of internal consistency and construct validity were performed. As general conclusions, the expert judgment provided a positive evaluation of the content, highlighting its general appropriateness and relevance to the research setting.